2013
DOI: 10.1002/anie.201306263
|View full text |Cite
|
Sign up to set email alerts
|

Hematite‐Based Water Splitting with Low Turn‐On Voltages

Abstract: Zusätzliche Lage: Die photoelektrochemische Aktivität von Hämatit in der Wasserspaltung wurde durch Modifikation der Oberfläche mit amorphem NiFeOx deutlich gesteigert (siehe Auftragung; FTO=fluordotiertes Zinnoxid; RHE=reversible Wasserstoffelektrode). Die gemessene Photospannung erhöht sich von 0.24 auf 0.61 V, woraus sich ein rekordverdächtig niedriges Einschaltpotential von 0.62 V ergibt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
375
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 416 publications
(399 citation statements)
references
References 29 publications
17
375
0
2
Order By: Relevance
“…Some demonstrated techniques for evaluating the interplay between these mechanisms include transient absorption spectroscopy, 100 impedance spectroscopy and transient photocurrent spectroscopy, 26 and photovoltage measurements. 58,101 In a "well" designed system ( Fig. 8a and b), there will be passivated surface trap states, a fast interfacial charge-transfer rate for water splitting, and a very slow rate of photocorrosion.…”
mentioning
confidence: 99%
“…Some demonstrated techniques for evaluating the interplay between these mechanisms include transient absorption spectroscopy, 100 impedance spectroscopy and transient photocurrent spectroscopy, 26 and photovoltage measurements. 58,101 In a "well" designed system ( Fig. 8a and b), there will be passivated surface trap states, a fast interfacial charge-transfer rate for water splitting, and a very slow rate of photocorrosion.…”
mentioning
confidence: 99%
“…Recent work reported that the onset potential of hematite can be drastically reduced to 0.62 V vs. RHE though loading a Ni-based catalyst, but the intrinsic onset potential of the hematite electrodes is 1.0 V vs. RHE. 18 Up to now, the preparation of hematite with intrinsically low onset potential has remained a great challenge.Herein we report a hematite photoanode with an intrinsic onset potential of as low as 0.58 V vs. RHE for PEC water oxidation. The passivation of the surface state and the gradient structure of the hematite photoanode using H 2 -O 2 flame treatment at high temperature are supposed to suppress surface charge recombination and promote the interfacial charge transfer, resulting in this low onset potential.…”
mentioning
confidence: 99%
“…Electronic surface states of photoelectrodes could cause a degree of the so-called Fermi level pining [65]. The accumulation of positive charges occurring at the photoanode/water interface at low bias potentials was found to be at its maximum when the photocurrent of photoanode onsets, thus possibly reducing or even canceling the effects of the space charge layer, and the potential drop occurs over the Helmholtz layer instead of in the photoelectrodes [10,66,67]. Under this condition, the holes captured by the surface states with energy within the band gap cannot drive the water oxidation reaction effectively; the surface states would then become the recombination sites for electrons and hole.…”
Section: Other Methodsmentioning
confidence: 96%